Exploiting the hierarchical morphology of single-walled and multi-walled carbon nanotube films for highly hydrophobic coatings - De Nicola, Francesco; Castrucci, Paola; Scarselli, Manuela; Nanni, Francesca; Cacciotti, Ilaria; De Crescenzi, Maurizio (Beilstein Journal of Nanotechnology, 2015)
Self-assembled hierarchical solid surfaces are very interesting for wetting phenomena, as observed in a variety of natural and artificial surfaces. Here, we report single-walled (SWCNT) and multi-walled carbon nanotube (MWCNT) thin films realized by a simple, rapid, reproducible, and inexpensive filtration process from an aqueous dispersion, that was deposited at room temperature by a dry-transfer printing method on glass. Furthermore, the investigation of carbon nanotube films through scanning electron microscopy (SEM) reveals the multi-scale hierarchical morphology of the self-assembled carbon nanotube random networks. Moreover, contact angle measurements show that hierarchical SWCNT/MWCNT composite surfaces exhibit a higher hydrophobicity (contact angles of up to 137°) than bare SWCNT (110°) and MWCNT (97°) coatings, thereby confirming the enhancement produced by the surface hierarchical morphology.
Keywords: hierarchical structures; hydrophobic surfaces; multi-walled carbon nanotube; single-walled carbon nanotube; wetting transitions

(untitled) - Wenzel, R. N. (Ind. Eng. Chem., 1936)

(untitled) - Feng, L.; Zhang, Y.; Xi, J.; Zhu, Y.; Wang, N.; Xia, F.; Jiang, L. (Langmuir, 2008)

(untitled) - Sun, M.; Luo, C.; Xu, L.; Ji, H.; Ouyang, Q.; Yu, D.; Chen, Y. (Langmuir, 2005)

(untitled) - Li, Y.; Huang, X. J.; Heo, S. H.; Li, C. C.; Choi, Y. K.; Cai, W. P.; Cho, S. O. (Langmuir, 2007)

(untitled) - Jung, Y. C.; Bhushan, B. (ACS Nano, 2009)

(untitled) - Egatz-Gomez, A.; Majithia, R.; Levert, C.; Meissner, K. E. (RSC Adv., 2012)

(untitled) - Bittoun, E.; Marmur, A. (Langmuir, 2012)

(untitled) - Shibuichi, S.; Onda, T.; Satoh, N.; Tsujii, K. (J. Phys. Chem., 1996)

(untitled) - Cassie, A. B. D.; Baxter, S. (Trans. Faraday Soc., 1944)

(untitled) - Bormashenko, E.; Bormashenko, Y.; Stein, T.; Whyman, G.; Bormashenko, E. (J. Colloid Interface Sci., 2007)

(untitled) - Gao, X.; Jiang, L. (Nature, 2004)

(untitled) - Lafuma, A.; Quéré, D. (Nat. Mater., 2003)

(untitled) - Giacomello, A.; Chinappi, M.; Meloni, S.; Casciola, C. M. (Phys. Rev. Lett., 2012)

(untitled) - Giacomello, A.; Meloni, S.; Chinappi, M.; Casciola, C. M. (Langmuir, 2012)

(untitled) - Savoy, E. S.; Escobedo, F. A. (Langmuir, 2012)

(untitled) - Murakami, D.; Jinnai, H.; Takahara, A. (Langmuir, 2014)

(untitled) - Bico, J.; Thiele, U.; Quéré, D. (Colloids Surf., A, 2002)

(untitled) - Bhushan, B. (Philos. Trans. R. Soc. London, Ser. A, 2009)

Biomimetics Biologically Inspired Technologies - Bar-Cohen, Y. (CRC Press, 2005)

(untitled) - Iijima, S. (Nature, 1991)

Carbon Nanotubes Advanced Topics in the Synthesis, Structure, Properties and Applications - Jorio, A.; Dresselhaus, G.; Dresselhaus, M. S. (Springer, 2008)

Physical Chemistry of Surfaces - Adamson, A. W.; Gast, A. P. (John Wiley & Sons, 1997)

(untitled) - Georgakilas, V.; Bourlinos, A. B.; Zboril, R.; Trapalis, C. (Chem. Mater., 2008)

(untitled) - Wang, N.; Xi, J.; Wang, S.; Liu, H.; Feng, L.; Jiang, L. (J. Colloid Interface Sci., 2008)

(untitled) - Yang, J.; Zhang, Z.; Men, X.; Xu, X.; Zhu, X. (J. Colloid Interface Sci., 2010)

(untitled) - Kakade, B. A.; Pillai, V. K. (J. Phys. Chem. C, 2008)

(untitled) - Nasibulin, A. G.; Kaskela, A.; Mustonen, K.; Anisimov, A. S.; Ruiz, V.; Kivistö, S.; Rackauskas, S.; Timmermans, M. Y.; Pudas, M.; Aitchison, B.; Kauppinen, M.; Brown, D. P.; et al. (ACS Nano, 2011)

(untitled) - Wang, C.-F.; Chen, W.-Y.; Cheng, H.-Z.; Fu, S.-L. (J. Phys. Chem. C, 2010)

(untitled) - Wang, K.; Hu, N.-X.; Xu, G.; Qi, Y. (Carbon, 2011)

(untitled) - Li, J.; Wang, L.; Jiang, W. (Carbon, 2010)

(untitled) - Wang, Z.; Koratkar, N.; Ci, L.; Ajayan, P. M. (Appl. Phys. Lett., 2007)

(untitled) - Zhang, L.; Resasco, D. E. (Langmuir, 2009)

(untitled) - Bu, I. Y. Y.; Oei, S. P. (Appl. Surf. Sci., 2010)

(untitled) - Kakade, B.; Mehta, R.; Durge, A.; Kulkarni, S.; Pillai, V. (Nano Lett., 2008)

(untitled) - Li, S.; Li, H.; Wang, X.; Song, Y.; Liu, Y.; Jiang, L.; Zhu, D. (J. Phys. Chem. B, 2002)

(untitled) - Li, Q.; DePaula, R.; Zhang, X.; Zheng, L.; Arendt, P. N.; Mueller, F. M.; Zhu, Y. T.; Tu, Y. (Nanotechnology, 2006)

(untitled) - Chakrapani, N.; Wei, B.; Carrillo, A.; Ajayan, P. M.; Kane, R. S. (Proc. Natl. Acad. Sci. U. S. A., 2004)

(untitled) - Bohn, S.; Platkiewicz, J.; Andreotti, B.; Adda-Bedia, M.; Couder, Y. (Phys. Rev. E, 2005)

(untitled) - Fusi, M.; Di Fonzo, F.; Casari, C. S.; Maccallini, E.; Caruso, T.; Agostino, R. G.; Bottani, C. E.; Bassi, A. L. (Langmuir, 2011)

(untitled) - Sauvage, F.; Di Fonzo, F.; Li Bassi, A.; Casari, C. S.; Russo, V.; Divitini, G.; Ducati, C.; Bottani, C. E.; Comte, P.; Graetzel, M. (Nano Lett., 2010)

(untitled) - De Nicola, F.; Castrucci, P.; Scarselli, M.; Nanni, F.; Cacciotti, I.; De Crescenzi, M. (Sci. Rep., 2014)

(untitled) - Clark, M. D.; Krishnamoorti, R. (Thin Solid Films, 2012)

(untitled) - Quéré, D. (Nat. Mater., 2002)

Capillarity and wetting phenomena - De Gennes, P.-G.; Brochard-Wyart, F.; Quéré, D. (Springer, 2003)

(untitled) - Huang, L.; Lau, S. P.; Yang, H. Y.; Leong, E. S. P.; Yu, S. F. (J. Phys. Chem. B, 2005)

(untitled) - Fürstner, R.; Barthlott, W.; Neinhuis, C.; Walzel, P. (Langmuir, 2005)

(untitled) - Zhang, H.; Lamb, R.; Lewis, J. (Sci. Technol. Adv. Mater., 2005)

(untitled) - Lai, Y.; Tang, Y.; Gong, J.; Gong, D.; Chi, L.; Lin, C.; Chen, Z. (J. Mater. Chem., 2012)

(untitled) - Huang, Y.; Zhou, J.; Su, B.; Shi, L.; Wang, J.; Chen, S.; Wang, L.; Zi, J.; Song, Y.; Jiang, L. (J. Am. Chem. Soc., 2012)

(untitled) - Stalder, A. F.; Melchior, T.; Müller, M.; Sage, D.; Blu, T.; Unser, M. (Colloids Surf., A, 2010)